Deciphering pain: molecular mechanisms and neurochemical pathways–challenges and future opportunities - Dehghan, Bahar; Abolhasanzadeh, Narges; Shademan, Behrouz; Nourazarian, Alireza (Frontiers in Molecular Biosciences, 2024)
This review delves into the intricate biological underpinnings of pain perception. It encompasses nociceptive signaling pathways, the molecular mechanisms involved, and the subjective experience of discomfort in humans. The initial focus is on nociceptor transduction, where specialized neurons transform noxious stimuli into electrical impulses. Subsequently, the review explores the central nervous system, elucidating how these signals are processed and modulated by critical elements such as ion channels, receptors, and neurotransmitters (e.g., substance P, glutamate, GABA). Shifting gears toward chronic pain, the review examines the concept of neuroplasticity, highlighting its potential to induce maladaptive responses through alterations in neural networks. The burgeoning field of pain genomics, alongside established genetic research, offers valuable insights that could pave the way for a framework of personalized pain management strategies. Finally, the review emphasizes the significance of these molecular insights in facilitating accurate therapeutic interventions. The overarching objective is to establish an integrative framework for precision medicine in pain management by incorporating this information alongside biopsychosocial models. This framework serves to translate the heterogeneous landscape of pain mechanisms into a coherent roadmap for the development of effective therapies.